The radio handbook - Collins, John; Bee, Arran (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Updated and revised, the fourth edition of The Radio Handbook is a comprehensive guide to the medium of radio and the radio industry in the UK. Featuring new chapters on social media and podcasting, this book offers a thorough breakdown of the knowledge and skills needed to work within the contemporary radio industry. Using examples, case studies and transcripts, it examines the various building blocks that make radio, from music scheduling to news values and from phone-ins to sports commentaries. The latest trends in contemporary audio practice are referenced throughout, including the increased adoption of smartphone technology, further consolidation within commercial radio, and the ongoing debate about the future funding of the BBC against the backdrop of an accelerated move towards remote working, the rise in popularity of podcasting and an ever more crowded media landscape. Combining theory and practice, this textbook is ideally suited for students of radio, media, communications, and journalism. It equips readers with the skills they need to not only produce good radio themselves, but to have the knowledge they need to become a critical friend of the medium"--
Radio style -- The role of the station -- The role of news -- Station and programme formats --Radio sport -- Bias and balance: accountability in radio journalism -- Social media: an audio revolution -- Catching a break: getting started in radio.
Includes bibliographical references and index.
Keywords: Radio broadcasting -- Handbooks, manuals, etc; Radio broadcasting -- Great Britain